2012
DOI: 10.1159/000343751
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Familial Tests of Association between Familial Idiopathic Scoliosis and Linked Regions on 9q31.3–q34.3 and 16p12.3–q22.2

Abstract: Objective: Custom genotyping of markers in families with familial idiopathic scoliosis were used to fine-map candidate regions on chromosomes 9 and 16 in order to identify candidate genes that contribute to this disorder and prioritize them for next-generation sequence analysis. Methods: Candidate regions on 9q and 16p–16q, previously identified as linked to familial idiopathic scoliosis in a study of 202 families, were genotyped with a high-density map of single nucleotide polymorphisms. Tests of linkage for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
1
9
1
Order By: Relevance
“…Previous studies suggest that the locus on 16p is a candidate region within a subgroup of families affected with FIS [14,18]. Although multiple TBX6 variants were identified in the families sequenced in this study, none of the TBX6 sequence variants segregated with the FIS phenotype.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Previous studies suggest that the locus on 16p is a candidate region within a subgroup of families affected with FIS [14,18]. Although multiple TBX6 variants were identified in the families sequenced in this study, none of the TBX6 sequence variants segregated with the FIS phenotype.…”
Section: Discussioncontrasting
confidence: 58%
“…These results identified a significant region on chromosome 16p. Fine-mapping of this region was completed in this AD subset, using custom SNP panels ( Supplemental Table 2 ) [18]. When the affectation status was defined as 20° of lateral spinal curvature, multipoint linkage analyses identified multiple SNPs (27.83 Mb to 31.32 Mb) that were significant at p≤0.001.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Esposito et al showed that steroid binding protein polymorphisms were effective in IS development (26). IS related zones were spotted in 6q, 10q and18q, 17p11.2, 19p13.3, 8q11, Xq23-26.1, 9q31.3-q34.3, 5q13-q14 and 3q11-q13, 9q31.2-q34.2, 17q25.3-qtel chromosomes (4, 7, 14, 38,58,68,87,103).…”
Section: Genetic-hormonal Causesmentioning
confidence: 99%